Corneal wound healing and nerve regeneration by novel ophthalmic formulations based on cross-linked sodium hyaluronate, taurine, vitamin B6, and vitamin B12 - Bucolo, Claudio; Maugeri, Grazia; Giunta, Salvatore; D’Agata, Velia; Drago, Filippo; Romano, Giovanni Luca (Frontiers in Pharmacology, 2023)
To evaluate the pharmacological profile of ocular formulations based on cross-linked sodium hyaluronate (CL-SH), taurine (Tau), vitamin B6 (Vit B6) and vitamin B12 (Vit B12) using in vitro and in vivo paradigms. Rabbit corneal epithelial cells were used to assess wound healing and reactive oxygen species (ROS) formation by scratch assay and oxidative stress (0.3 mM H2O2; 30 min), respectively with or without ocular formulations exposure. In vivo studies were carried out on albino rabbits to evaluate corneal nerve regeneration and corneal wound healing with or without treatment with six different formulations. Animals were anesthetized, the corneal epithelium was removed, and formulations were topically administered (30l/eye; 3 times/ day for 6 days). Slit-lamp observation was carried out at different time points. After six days the animals were killed, and corneas were collected to evaluate corneal re-innervation by immunohistochemistry of selective neuronal marker -III tubulin. Formulations containing the concentrations 0.16% or 0.32% of CL-SH, Tau, Vit B6 and Vit B12 accelerated corneal wound healing. Cells exposed to H2O2 led to significant (p<0.05) increase of ROS concentration that was significantly (p<0.05) counteract by formulations containing CL-SH (0.32%) and Tau with or without vitamins. The extent of re-innervation, in terms of β-III tubulin staining, was 5-fold greater (p<0.01) in the eye of rabbits treated with formulation containing 0.32% CL-SH, Tau, vitamins (RenerviX®) compared with the control group (no treatment). Furthermore, re-innervation elicited by RenerviX® was significantly greater (p<0.01) compared with the group treated with the formulation containing 0.32% CL-SH and Tau without vitamins, and with the group treated with the formulation containing 0.5% linear sodium hyaluronate (SH), Tau, and Vit B12, respectively. In conclusion, among the formulations tested, the new ophthalmic gel RenerviX was able to contrast oxidative stress, to accelerate corneal re-epithelization and to promote nerve regeneration.